A software program to measure the three-dimensional length of the spine from radiographic images: Validation and reliability assessment for adolescent idiopathic scoliosis. (January 2017) - Berger, Steve; Hasler, Carol-Claudius; Grant, Caroline A.; Zheng, Guoyan; Schumann, Steffen; Büchler, Philippe
Abstract: Background and objective: The aim of this study was to validate a new program which aims at measuring the three-dimensional length of the spine's midline based on two calibrated orthogonal radiographic images. The traditional uniplanar T1-S1 measurement method is not reflecting the actual three dimensional curvature of a scoliotic spine and is therefore not accurate. The Spinal Measurement Software (SMS) is an alternative to conveniently measure the true spine's length. Methods: The validity, inter- and intra-observer variability and usability of the program were evaluated. The usability was quantified based on a subjective questionnaire filled by eight participants using the program for the first time. The validity and variability were assessed by comparing the length of five phantom spines measured based on CT-scan data and on radiographic images with the SMS. The lengths were measured independently by each participant using both techniques. Results: The SMS is easy and intuitive to use, even for non-clinicians. The SMS measured spinal length with an error below 2 millimeters compared to length obtained using CT scan datasets. The inter- and intra-observer variability of the SMS measurements was below 5 millimeters. Conclusions: The SMS provides accurate measurement of the spinal length based on orthogonal radiographic images. The software is easy to use and could easily integrate the clinical workflow and replace current approximations of the spinal length based on a single radiographic image such as the traditional T1-S1 measurement.